Comparison of retinal nerve fiber layer thickness, macula thickness and optic nerve head parameters in opioid dependent and normal adult - Kuen, Wong Chee (2016)
Introduction Drug abuse is a socioeconomic problem that affects the public of the country. Heroin and morphine, which falls under the opioid group continues to be the commonest drug of abuse in Malaysia. Opioid usage is associated with addiction and dependence, and reported ocular side effects are pupillary miosis, conjunctiva hyperemia, ocular motility disorder and risk of complication such as endophtalmitis. It was also reported that chronic opioid usage leads to neurological degeneration. Objective To compare the retinal nerve fiber layer thickness, macula thickness and optic nerve head parameters in opioid dependent and normal adult. Method The study design was a case control with opioid dependent individuals and healthy individuals recruited from the Methadone Clinic, Department of Psychiatry and Ophthalmology Clinic, Department of Ophthalmology, Hospital Universiti Sains Malaysia. Thirty five opioid dependent subjects and thirty five healthy subjects with no history of opioid use were recruited. Ophthalmological examination and optical coherence tomography (Heidelberg Spectralis ® OCT) were performed. Results Compared to normal healthy subjects, opioid dependent group has thinner average retinal nerve fiber layer in the right eye (p<0.05) and in both superior quadrant of the optic nerve (p<0.05). Analysis of other segments did not show any statistical significance Conclusion Early thinning of the retinal nerve fiber layer could be one of the early signs of complication from long term opioid usage. Further studies may be needed to determine if further thinning occurs with time and the implication to the patients’ vision.